Application of Some Physicochemical Properties of Selected Soil Samples from Mesopotamian Agricultural Plain, Iraq, Indicating Soil Erosion and Degradation - Raghad S. Mouhamad; Khaldoun Ahmad (Journal of Agriculture and Rural Development Studies, 2024)
Twenty-four soil samples of 0-15 cm depth were collected from Mesopotamian agricultural plain, located in Kut-Iraq. Multiple methods determined in this study including partial size distribution size analysis, elemental analysis pH, soil electrical conductivity, Sodium Adsorption Ratio (SAR), organic matter, and Urease. High amount of salt causes the soil samples to be basic soil, pH ranges from 7 to 8, and not able to obtain adequate nutrients. All of soil samples have a dispersive property that means the soil are vulnerable to erosion by rainfall or run off. The high value of Soil electrical conductivity (EC) indicates the lack of microorganisms in soil to enhance soil health and indicate the soil damage in the study area. High Ca content in soil samples reduced K/Ca ratios which in terns impact the presence of K on soil samples. Statistical analysis between soil textures and physico-chemical properties indicate low value of erodibility (k) factor due to high concentrations of Ca. Over all, the soil in the Mesopotamian agricultural plain shows damage in the structure due to human activity and lack of vegetation covers.